Additive effect of knockdown resistance mutations, S989P, V1016G and F1534C, in a heterozygous genotype conferring pyrethroid resistance in Aedes aegypti in Thailand - Plernsub S. (2017)
© 2016 The Author(s). Background: Mutation in the voltage-gated sodium channel gene that results in knockdown resistance (kdr), is a major mechanism of pyrethroid resistance in several mosquito species. In Aedes aegypti, V1016G (occurring with and without S989P) and F1534C mutations are common and widely distributed throughout Asia. The G1016 allele is known to be associated with resistanc e to type I and II pyrethroids. The C1534 allele is primarily associated with resistance to type I pyrethroids and is known to be a recessive allele in conferring kdr. Methods: We performed crossing experiments using a P989 + G1016 homozygous mutant strain (UPK-R), a C1534 homozygous mutant strain (PMD-R) and a pyrethroid susceptible strain (PMD) to determine the insecticide susceptibility of different genotypic hybrids. Allele-specific PCR methods were used to confirm the genotypes. Metabolic resistance caused by oxidative enzymes and esterase enzymes was ruled out by the addition of piperonyl butoxide (PBO) and bis(4-nitrophenyl)-phosphate, BNPP), respectively. Results: The median lethal concentration (LC50) of deltamethrin susceptibility of a S/P989 + V/G1016 + F/F1534 double heterozygous hybrid from the UPK-R × PMD cross was 0.57 (95 % CI: 0.51-0.63) μgl -1 , which was about 12-fold lower than for UPK-R, 6.98 (6.10-8.04) μgl -1 , and only about 4-fold greater than the susceptible PMD, 0.13 (0.12-0.15) μgl -1 . This resistance returned to 0.08 (0.07-0.09) μgl -1 on the addition of PBO suggesting that the P989 + G1016 kdr alleles are recessive. The LC50 of the S/P989 + V/G1016 + F/C1534 triple heterozygous hybrid was 3.58 (3.21-3.95) μgl -1 , which was intermediate between that of the homozygous mutant genotypes, being 2-fold higher than the C1534 homozygote and 2-fold lower than the P989 + G1016 homozygote. These minor differences and the high LC50 values of the triple mutated heterozygote indicate there is some degree of functional equivalence of the P989 + G1016 and C1534 alleles in the heterozygote. Addition of PBO decreased the LC50 values by 2-fold, from 3.58 (3.21-3.95) to 1.52 (1.35-1.73) μgl -1 , suggesting that oxidase enzymes play a partial role in resistance. The results are consistent with the median lethal time (LT50) of the triple mutated heterozygote against 0.05 % deltamethrin paper. An adult susceptibility test also revealed that the triple mutated heterozygote was resistant to deltamethrin and permethrin. Conclusions: The combination of the three kdr alleles in the triple mutated heterozygote, S/P989 + V/G1016 + F/C1534, confers high resistance to pyrethroids. This heterozygous form is common in Ae. aegypti populations throughout Thailand and may have an adverse effect on the efficacy of a mosquito control program using insecticide-based approaches.